Perceived social support and psychological wellbeing of children orphaned by HIV/AIDS in Southwestern Uganda - Nyoni, Thabani (Vulnerable Child Youth Stud, 2019)
Evidence points to a correlation between perceived social support and children’s psychological well-being globally. However, only a few studies have examined the relationship between perceived social support (PSS) from multiple sources and children’s psychological outcomes. Even fewer studies have examined the relationship between perceived social support from multiple sources and the psychological outcomes of children orphaned by HIV/AIDS in Sub-Saharan Africa (SSA). This study examines whether PSS from multiple sources (parents/caregivers, teachers, friends and classmates) and family cohesion are independently and collectively associated with the psychological well-being of children orphaned by HIV/AIDS in Uganda. This study used baseline data from a National Institute of Health (NIH)-funded Suubi-Maka (Hope for families) study, conducted in Southwestern Uganda. A total of 346 child-caregiver dyads from 10 comparable primary schools participated in the study. Multivariate and multivariable regression analyses were conducted to examine: (1) variations in PSS from multiple sources and family cohesion, and (2) the relationship between PSS, family cohesion and children’s psychological outcomes, measured by depression, hopelessness, and self-concept. Controlling for participants’ demographic and household characteristics, the combined measure of PSS from multiple sources was positively associated with self-concept (b = .32, 95% CI = .23, .41, p ≤ .001) and negatively associated with hopelessness (b = −.19, 95% CI = −.29, −.09, p ≤ .001) and depressive symptoms (b = −.13, 95% CI = −.23, −.03, p ≤ .01). PSS from parents/guardians and teachers was a significant predictor. In addition, family cohesion was positively associated with self-concept (b = .37, 95% CI = .15, .58, p ≤ .001) and negatively associated with depressive symptoms (b = −.36, 95%CI = −.59, −.13, p≤ = .01). Findings indicate that family cohesion and perceived social support, especially from parent/caregivers and teachers were associated with better children’s psychological outcomes. In HIV-impacted communities, interventions designed to strengthen family relationships and social support are essential to offset children’s psychological well-being.